Answer:
-48x+16
Step-by-step explanation:
-8(6x - 2) first multiply each term in the parentheses by 8 to get -8x6x-8x(-2) and calculate the product to get your answer which is -48x+16
A+b=15----(1)
a*b=54----(2)
(1) a=15-b ----(3)
put(3) in(2)
(15-b)*b=54
15b-b^2=54
b^2-15b+54=0
(b-9)(b-6)=0
so b=9 or b=6
if b=9 then a=15-9=6
if b=6 then a=15-6=9
answer two numbers are 6 and 9
Answer:
21440
Step-by-step explanation:
<h2>
Simplify:</h2>
Start by multiplying 7x³ by x² and -5.
- 7x⁵ - 35x³ + (8x² - 3)(x² - 5)
Multiply 8x² by x² and -5.
- 7x⁵ - 35x³ + 8x⁴ - 40x² + (-3)(x² - 5)
Multiply -3 by x² and -5.
- 7x⁵ - 35x³ + 8x⁴ - 40x² -3x² + 15
Combine like terms together.
- 7x⁵ - 35x³ + 8x⁴ - 43x² + 15
Rearrange the terms in descending power order.
- 7x⁵ + 8x⁴ - 35x³ - 43x² + 15
<h2>Verify (I): </h2>
Substitute x = 5 into the above polynomial.
- 7(5)⁵ + 8(5)⁴ - 35(5)³ - 43(5)² + 15
Evaluate the exponents first.
- 7(3125) + 8(625) - 35(125) - 43(25) + 15
Multiply the terms together.
- 21875 + 5000 - 4375 - 1075 + 15
Combine the terms together.
This is the answer when substituting x = 5 into the simplified expression.
<h2>
Verify (II):</h2>
Substitute x = 5 into the expression.
- [7(5)³ + 8(5)² - 3][(5)² - 5]
Evaluate the exponents first.
- [7(125) + 8(25) - 3][(25) - 5]
Multiply the terms in the first bracket next.
Evaluate the expressions inside the brackets.
Multiply these two terms together.
This is the answer when substituting x = 5 into the original (unsimplified) expression.
Answer:
4 right; 4 up
Step-by-step explanation:
The difference between the two points is ...
P'(1, 5) -P(-3, 1) = (1-(-3), 5-1) = (4, 4)
The translation is 4 units to the right and 4 units up.